Przetrwały przewód tętniczy i niescalenie mięśnia lewej komory jako kardiologiczne objawy monosomii 1p36 - Mazurak, Magdalena; Kusa, Jacek; Skiba, Paweł; Śmigiel, Robert (Pediatria Polska - Polish Journal of Paediatrics, 2017)
1p36 monosomy is one of the most common deletion syndromes. Cardiac diseases occurred in about 45–75% of affected individuals. However, there is only a few papers in cardiac journals concerning heart problems associated to this syndrome. We describe an infant with dysmorphic features and two different cardiac anomalies (patent ductus arteriosus and left ventricular non-compaction) in which monosomy 1p36 was recognized.